CHARACTERIZATION OF BETA THALASSAEMIA MUTATIONS IN PATIENTS HAVING BORDERLINE HAEMOGLOBIN A2 LEVELS - Noor, Afshan; Manzar Bozdar; Hamid Saeed Malik; Rafia Mehmood; Ayesha Khursheed; Ayesha Khan; Nighat Seema; Irshad, Romana (Journal of Ayub Medical College Abbottabad, 2024)
Background: The occurrence of a single beta thalassaemia allele is frequently related with microcytic hypochromic red blood cells and a rise in HbA2 levels. In some beta thalassaemia carriers, the outcome of this allele or its collaboration with other acquired or genetic defects may result in normal or borderline Haemoglobin bA2 levels. Objective was to establish the importance of molecular analysis in borderline HbA2 individuals and its significance in a population screening program. Methods: It was a cross-sectional study conducted over a period of six months, from July-December 2023. All 123 individuals with borderline HbA2 levels between (3‒3.9%) diagnosed by High-performance liquid chromatography (HPLC)/Capillary Zone Electrophoresis underwent molecular testing using multiplex amplification refractory mutation system-Polymerase Chain Reaction (ARMS-PCR) to detect common beta thalassaemia mutations: Fr8-9, IVS1-5, Fr41-42, Cd15, Cd5, IVS1-1, IVS1-1, Cd30, Cd30, Fr16, IVSII-1, Del619, and CAP+1 in the Department of Haematology, Armed Forces Institute of Pathology, Rawalpindi .Statistical tests were applied to compare Red Blood Cell indices and Haemoglobin A2 values among beta thalassaemia carriers and non-carriers. Results: Among those tested, 47.1% (n=58) were found to carry Beta thalassaemia mutations. The most prevalent mutations were IVS1-5 (n=19,15.4%) and Fr8-9 (n=19,15.4%) followed by Fr41-42 (n=08,6.5%). Subjects with mutations exhibited significantly lower mean corpuscular volume and mean corpuscular haemoglobin compared to those without mutations (p-value= <0.001). Beta thalassaemia mutations were seen more frequently when HbA2 was in range of 3.5-3.9% (n=37,63.8%), as compared to HbA2 that was 3-3.4% (n=21,36.2%) and this difference was found to be significant (p-value= <0.001). The CAP+1 mutation was associated (n=02,1.6%) with normal mean MCV and MCH compared to other identified mutations. Conclusions: It is concluded that molecular study for the common beta thalassaemia mutations in Pakistani population plays a pivotal role in confirmation of borderline HbA2 thalassaemia carriers, specifically in areas with a high prevalence of the disease. Molecular testing for beta thalassaemia should be offered to all individuals with borderline HbA2 with values especially between 3.4‒3.9% and having microcytic hypochromic indices.